The Influence of Perceived Quality of Service on Purchasing Decisions at Skage Fried Chicken: The Role of Customer Engagement as an Intervening Variable - Parinsi, Welimas Kristina; Lestari Musa, Dwi Anugrah; Pratiwi Musa, Kartika Septiary (International Humanity Advance, Business & Sciences, 2025)
This study analyzes the influence of perceived service quality (Quality of Service) on consumer purchasing decisions at Skage Fried Chicken, with customer engagement as an intervening variable. In the context of an increasingly competitive culinary industry, it is important for companies to understand the factors that influence consumer purchasing decisions. Data were collected through a survey involving 100 students of the Management Study Program, Makassar State University who had made purchases at the restaurant. The analysis method used is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), which allows researchers to test the relationship between variables simultaneously. The results of the study indicate that service quality has a positive and significant influence on purchasing decisions, and customer engagement acts as a mediator that strengthens the relationship between service quality and purchasing decisions. These findings emphasize the importance of improving service quality to not only attract customers but also increase their engagement and purchasing decisions